Pembuatan Serbuk Cangkang Keong Mas (Pomacea canaliculata L.) serta Aplikasinya sebagai Penjernih Air Sungai dan Pengikat Logam Berat Kadmium - Eko Nopriansyah; Ace Baehaki; Rodiana Nopianti (Universitas Sriwijaya, 2016)
This study aims to produce golden snail shell powder that can be used as a purifier and a metal binder on Musi River water. The method used was a randomized block design with two factors, namely the type of purifier treatment (A) consist of golden snails shell powder and shrimp shell chitosan. Purifier concentration factor (B) is 0%, 0.5% and 1%. Data obtained through several stages in a row of manufactured of golden snail powder, application of golden snail shell powder and shrimp shell chitosan, and analyzed the effect of golden snail shell powder and shrimp shell chitosan on turbidity, TDS, pH and Cd concentration of water river. 80 grams of golden snail shell obtained 20 grams of golden snail shell powder. The golden snail shell powder produced known as calcium carbonate (CaCO3). Aplication of golden snail shell powder in water river able to lowering the turbidity 75% at 0.5% concentration and 78% at 1% concentration, increase the value of TDS is still within the threshold in range of 391.5 to 604 ppm, and increasing the pH in range of 5-7 which is still within the tolerance limits corresponding Government Regulation Number 416 of 1990. However, the golden snails shell powder raise the river water Cd concentration from 0.00782 to 0.00815 ppm, while the shrimp shell chitosan capable to lowering the concentration of Cd in river water of 0.00048-0.000518 ppm.